20 Years of Secretagogin: Exocytosis and Beyond - Maj, Magdalena; Wagner, Ludwig; Tretter, Verena (Frontiers in Molecular Neuroscience, 2019)
Calcium is one of the most important signaling factors in mammalian cells. Specific temporal and spatial calcium signals underlie fundamental processes such as cell growth, development, circadian rhythms, neurotransmission, hormonal actions and apoptosis. In order to translate calcium signals into cellular processes a vast number of proteins bind this ion with affinities from the nanomolar to millimolar range. Using classical biochemical methods an impressing number of calcium binding proteins (CBPs) have been discovered since the late 1960s, some of which are expressed ubiquitously, others are more restricted to specific cell types. In the nervous system expression patterns of different CBPs have been used to discern different neuronal cell populations, especially before advanced methods like single cell transcriptomics and activity recording were available to define neuronal identity. However, understanding CBPs and their interacting proteins is still of central interest. The post-genomic era has coined the term „calciomics“, to describe a whole new research field, that engages in the identification and characterization of calcium binding proteins and their interactome. Secretagogin is a CBP, that was discovered 20 years ago in the pancreas. Consecutively it was found also in other organs including the nervous system, with characteristic expression patterns mostly forming cell clusters. Its regional expression and subcellular location together with the identification of protein interaction partners implicated, that secretagogin has a central role in hormone secretion. Meanwhile, with the help of modern proteomics a large number of actual and putative interacting proteins has been identified, that allow to anticipate a much more complex role of secretagogin in developing and adult neuronal cells. Here we review recent findings that appear like puzzle stones of a greater picture.